Counseling and Education on the Dangers of Free Association for Mental Health and Strengthening Adolescents in Cirebon Regency, West Java - Sukanti, Lina; Riyanto, Slamet; Sutarman; Rahayu, Monita; Athar Ismail Muzakir, Muhammad (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
T The purpose of this research is to (1). Provide education and assistance to the community which includes counseling activities regarding the dangers of free Association for the younger generation (2). Providing services to the community includes consulting services, health services, career guidance, cooperative development services, and entrepreneurial development. This research method uses a qualitative approach, to describe the phenomenon of events in the research field. Data collection technique. Interviews with guidance participants, village officials, and people who are infected with the disease. Field observations to observe events that arise in the local community. Documentation studies in the form of archives in Setu Patok District, Cirebon Regency, and books that are the focus of community service research. Conclusion: Free Association behavior in adolescents because they do not understand Association education, and the rapid development of the era. Factors that cause free Association that can be known that pay attention to and avoid adolescent behavior. The impact of free Association on teenagers damages the future. Need to be given a good and correct understanding of free Association.